2020
DOI: 10.1016/j.compscitech.2020.108200
|View full text |Cite
|
Sign up to set email alerts
|

Durability sensor using low concentration carbon nano additives

Abstract: In this paper, nanocomposite durability sensors were developed in order to detect the diffusion of chemicals in real-time. Polymer nanocomposite based sensors usually consist of conductive nano-additives such as CNT (carbon nanotube), graphene, carbon black, silver nanoparticles, etc. However, these nanocomposite sensors use a high content of nanomaterials to ensure good conductivity. In this study, a special approach for a chemical sensor with a low concentration (0.1 wt%-2 wt%) carbon nano-additive was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Previously, we have explored the use of carbon nanomaterials and conjugated polymer in detecting the acid penetration in the polymer nanocomposites [13][14][15][16]. Based on our experimental and modeling results, we have confirmed that the change in conductivity of the polymeric matrix can be used as a primary indicator to monitor the acid penetration in the composite.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Previously, we have explored the use of carbon nanomaterials and conjugated polymer in detecting the acid penetration in the polymer nanocomposites [13][14][15][16]. Based on our experimental and modeling results, we have confirmed that the change in conductivity of the polymeric matrix can be used as a primary indicator to monitor the acid penetration in the composite.…”
Section: Introductionmentioning
confidence: 53%
“…Previously, we have explored the diffusion of acid aqueous in epoxy based carbon nanocomposite [13,16]. We find that the diffusion of some ions is much faster than the others.…”
Section: Sensing Mechanismmentioning
confidence: 96%
“…Table 4 compiled the different properties between some selected CNMs. Thus, promoting and exploiting the CNMs into various applications in our daily life such as in sensors [91], catalyst [92], fillers in composites [93], and energy conversion and storage [94,95] to drug carries in cancer treatment [96]. Owing to the excellent performance of the CNMs, they have received a lot of attention from researchers.…”
Section: Carbon-based Nanostructured Materialsmentioning
confidence: 99%
“…High corrosion resistance and chemical durability are imperative characteristics to withstand saline, corrosive and aggressive acids. Although polymer composite provides a high corrosion barrier and durability, unexpected structural failure before the designed service lifetime has been reported [12][13][14]. Direct contact with chemicals provokes unavoidable diffusion phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…To identify and mitigate failure, structural health monitoring (SHM) techniques are deployed to evaluate the structural condition. Usually, SHM employs the implementation of sensors and actuators, however, chemical storage facilities often evaluate the structural health with weight and volume measurements, and colour-based methods [14,[17][18][19]. Although these methods can reasonably predict the structural state, they are mostly used post-use and impractical, as they require disassembly of the structure and complex machinery, resulting in time-consuming and expensive approaches.…”
Section: Introductionmentioning
confidence: 99%